Polıtıcal Dıscourse and Cognıtıve Lınguıstıcs - Nigar Babayeva (MANDALIKA : Journal of Social Science, 2024)
One of the fundamental problems of culture is the management of discourse. An individual can sometimes become an object of manipulation by the person controlling the discourse. During the proper discourse, it is possible to control and guide both people with mental disorders and those in custody. In modern scientific literature, the term discourse replaces the terms "style" and "language". For example, if earlier the expressions Shakespeare's style or Shakespeare's language were used, now the expressions political discourse, Ronaldo Reagan's discourse are more popular. In the research work, analysis of questions such as "Whose discourse? How discourse?" is given place, including the  the study of discourse experience. Discourse - has stylistic features behind which there is a certain ideology. Here, the topic of the discussion, methods, scope of influence, etc. play an important role.